Novel double-layer composite film and application thereof

Cellulose palmitate is prepared by using carboxymethylcellulose grafted palm oil to load curcumin and cellulose grafted palm oil in chitosan food packaging film to form a composite film with a double-layer structure, which solves the problems of insufficient barrier performance and lack of intelligent indicator function of chitosan film, and achieves efficient food preservation and deterioration detection.

CN119704792AActive Publication Date: 2025-03-28SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411829111.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing chitosan food packaging films have insufficient water vapor barrier performance and lack intelligent indication functions to detect food spoilage.

Method used

Carboxymethylcellulose grafted palm oil is used to prepare amphiphilic fibers for loading curcumin, improving the dispersion of curcumin in chitosan solution, and cellulose palmitate is prepared by cellulose grafted palm oil to form a composite film with a bilayer structure, improving barrier properties and achieving color response.

Benefits of technology

The barrier properties of water vapor and oxygen of chitosan film are significantly improved, and the color response of curcumin indicates food spoilage, providing a simple method for food preservation and spoilage detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704792A_ABST
    Figure CN119704792A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of bio-based packaging materials, and particularly relates to a novel double-layer composite film and application thereof. The preparation method of the novel double-layer composite membrane comprises the following steps: reacting palmitoleic anhydride with carboxymethyl cellulose to obtain carboxymethyl cellulose palmitate; then adding a pH sensitive natural dye indicator to obtain a nano emulsion containing pH sensitive carboxymethyl cellulose palmitate; then loading a natural polymer material to prepare a film-forming material; and finally, on the basis of cellulose palmitate film forming, adding the film forming material to prepare a composite film, thereby obtaining the novel double-layer composite film. The double-layer composite film can be self-emulsified without additionally adding a surfactant, and has the capability of loading functional indication (pH sensitive color indication) substances; meanwhile, the water vapor and oxygen barrier property of a coating material, such as a chitosan film, is improved, and the coating material has a very good prospect in food or fruit fresh-keeping application. According to the method provided by the invention, raw materials are green, and a tape casting method is adopted, so that the method can be applied to industrial production and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of bio-based packaging materials, and more specifically, relates to a novel double-layer composite film and application thereof. Background Art

[0002] Among packaging materials, the extensive use of petroleum-based plastics has led to environmental problems. With the improvement of people's environmental awareness, degradable bio-based materials have become a hot topic in the packaging industry. Chitosan is one of the most abundant polysaccharides in nature. Due to its excellent film-forming ability, the application of chitosan in food packaging has attracted much attention. With the continuous improvement of people's living standards, people pay more and more attention to the safety of food, so the requirements for food packaging films are also increasing. Food packaging is very important for maintaining the integrity of food and protecting it from biological and chemical damage. However, the ability of chitosan film to block water vapor is insufficient, which is not conducive to extending the shelf life of food. Food spoilage detection requires complicated detection procedures and instruments. Packaging films that can respond to food corruption are a simple way. Adding active substances to the chitosan film matrix can further broaden the functionality of the composite film. At present, most of the methods for adding natural active substances to chitosan films adopt the form of nano-encapsulation, such as adding some natural pigments. When the environment changes, the color of the pigment will change accordingly. The pigments currently widely used are anthocyanins, curcumin, carotene, etc.

[0003] Cellulose is one of the largest renewable resources, and its structure has many hydrogen bonds that give it hydrophilicity. Palm oil is a bio-based raw material with a triglyceride structure, which has good hydrophobicity. In view of the current demand for food packaging, it is very necessary to prepare a packaging film that is all bio-based, green, has good barrier properties, and is color-responsive. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present application provides a novel double-layer composite membrane. The present application adopts two strategies. First, carboxymethyl cellulose is grafted with palm oil to prepare amphiphilic fibers for loading curcumin, thereby improving the dispersibility of curcumin in chitosan solution. Since curcumin undergoes deprotonation in an alkaline environment, the wavelength of light absorption changes and the color turns red. Therefore, the addition of curcumin can make the chitosan membrane have color response performance. Second, cellulose is grafted with palm oil to prepare cellulose palmitate, and chitosan membrane and cellulose palmitate membrane are used to prepare a composite membrane with a double-layer structure. The addition of long carbon chains can provide the hydrophobicity of the material. The addition of cellulose palmitate membrane greatly improves the barrier performance of the chitosan membrane, and for the first time, a fully bio-based double-layer membrane is prepared using cellulose ester and chitosan.

[0005] Therefore, the primary purpose of this application is to provide a novel double-layer composite film chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate preparation. Compared with the preparation of other chitosan composite films, ours uses all-biobased materials, which is in line with the trend of environmentally friendly development, and the introduction of cellulose palmitate greatly improves the barrier properties of the chitosan film.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a novel double-layer composite membrane comprises the following steps:

[0008] S1, using palm oil as a raw material to prepare palmitoleic acid, and then further preparing palmitoleic acid into palmitoleic anhydride;

[0009] S2: reacting the palmitoleic anhydride obtained in step S1 with carboxymethyl cellulose, and obtaining carboxymethyl cellulose palmitate after purification.

[0010] S3: adding the carboxymethyl cellulose palmitate obtained in step S2 to a pH-sensitive natural dye indicator to obtain a pH-sensitive carboxymethyl cellulose palmitate nanoemulsion;

[0011] S4: adding natural polymer materials to the pH-sensitive carboxymethyl cellulose palmitate nanoemulsion obtained in step S3 to prepare a film;

[0012] S5: Forming cellulose palmitate into a film, and then adding the film-forming material obtained in step S4 onto the film to prepare a composite film, thereby obtaining the novel double-layer composite film.

[0013] The preparation of cellulose palmitate in step S5 refers to step S1 and step S2, wherein carboxymethyl cellulose is replaced by cellulose.

[0014] Preferably, the pH-sensitive natural dye indicator in step S3 is any one or more of anthocyanin, curcumin, carotene and shikonin.

[0015] Preferably, the natural polymer material in step S4 is any one or more of agarose, chitosan, starch, cellulose, pectin, gelatin, zein and alginate.

[0016] Preferably, curcumin is added in step S3, and the process of adding curcumin is: firstly dissolving carboxymethyl cellulose palmitate and curcumin respectively, and then mixing and homogenizing; the mass ratio of carboxymethyl cellulose palmitate and curcumin is 5 to 15: 1. The present invention uses curcumin to give color responsiveness to the chitosan film. When food with high nitrogen content is corrupted, volatile alkaline nitrogen is generated. When encountering an alkaline environment, curcumin changes from yellow to red, thereby enabling intelligent indication.

[0017] Preferably, chitosan is added in step S4, and the mass fraction of chitosan is 2-5wt%.

[0018] Preferably, the molar ratio of carboxymethyl cellulose to palmitoleic anhydride in step S2 is 1:3-6.

[0019] Preferably, in step S2, p-toluenesulfonic acid is used as a catalyst and dimethyl sulfoxide is used as a co-solvent for dissolution; wherein the mass ratio of palmitoleic anhydride to p-toluenesulfonic acid is 12:1, and the mass ratio of carboxymethyl cellulose to dimethyl sulfoxide is 1:10.

[0020] Preferably, the film formation in step S5 is carried out by a casting method.

[0021] The present application also claims protection for the novel double-layer composite membrane obtained by the preparation method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The long carbon chain used in the present invention comes from palm oil, a biomass resource. The reaction raw materials are renewable and have no pollution to the environment. The waste liquid treatment and recycling in the preparation process is simple and convenient, which is conducive to industrial production.

[0024] The palm oleic anhydride synthesized by the present invention has the characteristics of high reactivity compared with palm oil itself. Unmodified palm oil cannot react with carboxymethyl cellulose, and the reaction process conditions are friendly. Compared with the hydrophobic modification of other carboxymethyl celluloses, it is greener chemistry.

[0025] The carboxymethyl cellulose palmitate synthesized by the invention can be self-emulsified without adding an additional surfactant, and has the ability to load hydrophobic drugs, thereby improving the dispersibility of the curcumin solution in the chitosan solution.

[0026] The cellulose palmitate synthesized by the present invention has hydrophobicity, greatly improves the water vapor and oxygen barrier properties of the chitosan film, and is very promising for the preservation of some fruits.

[0027] The invention not only uses green raw materials, but also adopts a casting method, which can be applied to industrial production and large-scale preparation. This method is simple to prepare a fully bio-based two-layer membrane structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are infrared images of Examples 4, 5, 6 and Comparative Example 1.

[0029] Figure 2 These are SEM images of Examples 4, 5, and 6.

[0030] Figure 3 The mechanical properties diagram of Examples 4, 5, and 6.

[0031] Figure 4 Hygroscopicity and water solubility of Examples 4, 5, and 6.

[0032] Figure 5 This is a color responsiveness effect diagram of Example 6. DETAILED DESCRIPTION

[0033] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the figures. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are prepared according to the conditions recommended by the normal conditions or the manufacturers. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0034] Example 1

[0035] Weigh 60g palm oil, 50ml anhydrous ethanol, 11g 50 ml of deionized water was dissolved in NaOH, mixed evenly, and reacted at 70° C. for 1.5 h, phosphoric acid was used to adjust the pH to 3 to terminate the reaction, and the solution was split 4 times with deionized water at 80° C., and water was removed by rotary evaporation for 2 h to obtain palmitoleic acid; palmitoleic acid was weighed, 50 wt % of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDI) salt was added, and the solution was reacted at 70° C. for 20 min, and the solution was centrifuged at 8000 rpm for 5 min while hot, and 33.3 wt % of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDI) salt was added for the second time, and the solution was centrifuged at 8000 rpm for 5 min while hot to obtain palmitoleic anhydride; 3 g of carboxymethyl cellulose, 2 g of p-toluenesulfonic acid, and 90 ml of dimethyl sulfoxide were weighed, and the carboxymethyl cellulose was completely dissolved, and 24 g of palmitoleic anhydride was added, and the solution was reacted at 110° C. for 2.5 h, and the solution was washed with dichloromethane, and the product was purified by centrifugation to finally obtain a purified carboxymethyl cellulose palmitate sample.

[0036] Example 2

[0037] Weigh 60g of palm oil, 50ml of anhydrous ethanol, and 11g of NaOH dissolved in 50ml of deionized water, mix well, react at 70°C for 1.5h, adjust the pH to 3 with phosphoric acid to terminate the reaction, split with 80°C deionized water 4 times, and remove water by rotary evaporation for 2h to obtain palmitoleic acid; weigh palmitoleic acid, add 50wt% 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDI) salt, react at 70°C for 20min, centrifuge at 8000rpm for 5min while hot, and add 33.3wt% 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDI) salt for the second time. dimethylaminopropyl) carbodiimide hydrochloride (EDI) salt, centrifuge at 8000rpm for 5min while hot to obtain palmitoleic anhydride; weigh 3.4g of microcrystalline cellulose, 11.18g of DBU, and 30g of dimethyl sulfoxide, dissolve the microcrystalline cellulose in a carbon dioxide switch solvent system, and after the microcrystalline cellulose solution is completely clear and transparent, 30g of palmitoleic anhydride is added dropwise with a constant pressure dropping funnel, and reacted at 60°C for 4h. After the reaction is completed, it is washed and purified with anhydrous ethanol to obtain cellulose palmitate.

[0038] Example 3

[0039] 20 mg of carboxymethyl cellulose palmitate prepared in Example 1 was weighed and dissolved in deionized water, 2 mg of curcumin was dissolved in dichloromethane, the two solutions were mixed and homogenized for 7 min, dichloromethane was removed by rotary evaporation, and the precipitate was removed by an organic nylon filter to obtain a curcumin@carboxymethyl cellulose palmitate emulsion.

[0040] Example 4

[0041] 1 g of cellulose palmitate prepared in Example 2 was weighed, dissolved in 10 ml of tetrahydrofuran, spread on a smooth glass plate by a casting method, and dried to form a film at a temperature of 30° C. and an ambient humidity of 40-50%.

[0042] Example 5

[0043] Use 1% acetic acid aqueous solution to prepare 3wt% chitosan solution, add 60% glycerol, add curcumin@carboxymethylcellulose palmitate solution to the chitosan solution, stir and disperse evenly, spread on a smooth glass plate by casting method, dry at 30℃ and 40-50% humidity to form a film.

[0044] Example 6

[0045] A 3wt% chitosan solution was prepared with a 1% acetic acid aqueous solution, and 60% glycerol was added. The curcumin@carboxymethyl cellulose palmitate solution prepared in Example 3 was added to the chitosan solution, and the mixture was stirred and dispersed evenly. The cellulose palmitate film of Example 4 was prepared by a casting method, and after it was completely dried, a chitosan (curcumin@carboxymethyl cellulose palmitate) solution was laid on top of the film by the same casting method, and dried for 24 hours at a temperature of 30°C and an ambient humidity of 40-50%, to obtain a chitosan (curcumin@carboxymethyl cellulose palmitate)-cellulose palmitate double-layer composite film.

[0046] Comparative Example 1

[0047] A 3wt% chitosan solution is prepared with a 1% acetic acid aqueous solution, 60% glycerol is added, and the solution is spread on a smooth glass plate by a casting method. The solution is dried to form a film at a temperature of 30°C and an ambient humidity of 40-50%.

[0048] Test methods and conditions:

[0049] The infrared spectra of chitosan film, cellulose palmitate film, chitosan (curcumin @ carboxymethyl cellulose palmitate) film, and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film were measured by Nicolet IS10 spectrometer (Thermo Fisher, USA).

[0050] The SEM of cellulose palmitate film, chitosan (curcumin @ carboxymethyl cellulose palmitate) film, and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film were measured using a scanning electron microscope (EVO MA15, ZEISS). The EDX scan of the chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film is a distribution map of the K element. K element was added to the chitosan (curcumin @ carboxymethyl cellulose palmitate) film in the double-layer composite film, thereby obtaining a cross-sectional EDX scan of the double-layer composite film.

[0051] The mechanical properties of cellulose palmitate membrane, chitosan (curcumin @ carboxymethyl cellulose palmitate) membrane, and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate membrane were measured using an electronic universal testing machine equipped with a 2500N pressure sensor.

[0052] The samples were cut into small pieces for testing water solubility and hygroscopicity. For water solubility test of cellulose palmitate film, chitosan (curcumin @ carboxymethyl cellulose palmitate) film, chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film, the films were dried at 100 ° C for 24 h to reach a constant weight (m0), and the dried samples were placed in 50 mL of water at room temperature for 24 h, with occasional slight shaking, and the samples dissolved for 24 h were dried at 100 ° C to reach a constant weight (m1), and calculated using formula (1). For hygroscopicity test of cellulose palmitate film, chitosan (curcumin @ carboxymethyl cellulose palmitate) film, chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film, the films were dried at 105 ° C for 24 h and weighed (m0), then, they were stored in an environment with a humidity of 70-80% at room temperature for 24 h, and weighed again (m1).

[0053]

[0054] The water vapor barrier properties of cellulose palmitate film, chitosan (curcumin @ carboxymethyl cellulose palmitate) film, and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film were tested using GB / T 1037 on a Jinan Labthink (C360) instrument.

[0055] The oxygen barrier properties of cellulose palmitate film, chitosan (curcumin @ carboxymethyl cellulose palmitate) film, and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film were tested using GB / T 1038 in Burgger, Germany.

[0056] The color responsiveness of cellulose palmitate film, chitosan (curcumin @ carboxymethyl cellulose palmitate) film, and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film is characterized by combining the following four graphs (e.g. Figure 5 ):

[0057] (a) Color change of lyophilized curcumin@carboxymethylcellulose palmitate powder dissolved in phosphate buffer at different pH values ​​at a concentration of 1 mg / ml;

[0058] (b) Color change of chitosan (curcumin@carboxymethylcellulose palmitate)-cellulose palmitate membranes immersed in buffers with different pH values ​​for 5 min;

[0059] (c) UV spectra corresponding to different solutions in Figure a;

[0060] (d) Color change RGB and sensitivity of chitosan (curcumin@carboxymethyl cellulose palmitate)-cellulose palmitate film at 1 cm above 0.8 mol / L ammonia water at different times.

[0061] Analysis of measurement results

[0062] Figure 1 FTIR spectra of chitosan film (CS), cellulose palmitate film (MCCPOA), chitosan (curcumin @ carboxymethyl cellulose palmitate) membrane CS (Cur @ CMCPOA), and chitosan (curcumin @ carboxymethyl cellulose palmitate) -cellulose palmitate membrane (CS (Cur @ CMCPOA) - MCCPOA).

[0063] FT-IR spectroscopy was used to analyze the molecular interactions within the composite film. Figure 1 As shown, the acetyl CO peak of CS (amide I) appears at 1631 cm -1 , NH stretching vibration (amide II) peak appears at 1596 cm -1 The peak of the ester bond C=O of MCCPOA appears at 1740 cm -1 , indicating that palm oil was successfully grafted onto microcrystalline cellulose; 1631cm -1 and 1596cm -1 The peaks are amide I and amide II of CS, and the peak position of the benzene ring on curcumin is also at 1596 cm -1 CS (Cur@CMCPOA) 1743cm -1 is the ester peak on CMCPOA; 1753cm on CS (Cur@CMCPOA-MCCPOA) -1 and 1738cm -1 The ester peaks on MCCPOA and CMCPOA correspond to 1630 cm on CS (Cur@CMCPOA-MCCPOA). -1 and 1594cm -1 The peaks are amide I and amide II of CS, and the peak of the benzene ring on curcumin is also at 1594 cm -1 The CO asymmetric stretching vibration on CS is from 1631cm -1 and 1596cm -1 Offset is 1630cm -1 and 1594cm -1 , indicating that there are hydrogen bonding interactions between CS and Cur@CMCPOA and Cur@CMCPOA.

[0064] Figure 2SEM images of cellulose palmitate membrane (MCCPOA), chitosan (curcumin @ carboxymethyl cellulose palmitate) membrane CS (Cur @ CMCPOA), and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate membrane (CS (Cur @ CMCPOA) -MCCPOA). In Figure (a), a and b are scanning electron microscope images of the surface of MCCPOA film at different co-factors, and c is a scanning electron microscope image of the cross-section of MCCPOA film; in Figure (a), d and e are scanning electron microscope images of the surface of CS (Cur@CMCPOA) film at different co-factors, and f is a scanning electron microscope image of the cross-section of CS (Cur@CMCPOA) film; in Figure (b), a and b are scanning electron microscope images of the surface of MCCPOA film at different co-factors in CS (Cur@CMCPOA)-MCCPOA composite film, and c is a scanning electron microscope image of the cross-section of CS (Cur@CMCPOA)-MCCPOA composite film; d and e are scanning electron microscope images of the surface of CS (Cur@CMCPOA) film at different co-factors in CS (Cur@CMCPOA)-MCCPOA composite film; f is an EDX scan image of the cross-section of CS (Cur@CMCPOA)-MCCPOA composite film. The results of scanning electron microscopy show that the surfaces of MCCPOA membrane, CS (Cur@CMCPOA) membrane and CS (Cur@CMCPOA)-MCCPOA membrane are dense and smooth. From the cross-sectional electron microscopy of CS (Cur@CMCPOA)-MCCPOA membrane, it can be seen that CS (Cur@CMCPOA)-MCCPOA membrane successfully prepared a double-layer composite membrane. From the distribution of EDI, it can be seen that the fusion between the two layers of the membrane is good, indicating that the double-layer composite membrane was successfully prepared by casting.

[0065] Figure 3 The figure shows the mechanical properties of cellulose palmitate membrane (MCCPOA), chitosan (curcumin @ carboxymethyl cellulose palmitate) membrane CS (Cur @ CMCPOA), and chitosan (curcumin @ carboxymethyl cellulose palmitate) -cellulose palmitate membrane (CS (Cur @ CMCPOA) - MCCPOA). As can be seen from the figure, the stress of MCCPOA-CS (Cur @ CMCPOA3) membrane is 10.7MPa higher than that of CS (Cur @ CMCPOA3), and the elongation at break is increased by 30.55%, indicating that the double-layer structure is beneficial to improve the stress and elongation at break. Figure 2 The good fusion results of the double-layer structure can also be proved indirectly.

[0066] Figure 4The hygroscopicity and water solubility of cellulose palmitate membrane (MCCPOA), chitosan (curcumin @ carboxymethyl cellulose palmitate) membrane CS (Cur @ CMCPOA), chitosan (curcumin @ carboxymethyl cellulose palmitate) -cellulose palmitate membrane (CS (Cur @ CMCPOA) - MCCPOA) membrane. The water solubility of MCCPOA-CS (Cur @ CMCPOA3) is 13.05% lower than that of CS (Cur @ CMCPOA3), and the hygroscopicity of MCCPOA-CS (Cur @ CMCPOA3) is 5.85% lower than that of CS (Cur @ CMCPOA3). The results show that the introduction of MCCPOA is beneficial to improve the water solubility and hygroscopicity of the membrane.

[0067] Table 1 shows the water vapor barrier and oxygen barrier properties of cellulose palmitate film (MCCPOA), chitosan (curcumin @ carboxymethyl cellulose palmitate) film CS (Cur @ CMCPOA), and chitosan (curcumin @ carboxymethyl cellulose palmitate)-cellulose palmitate film (CS (Cur @ CMCPOA)-MCCPOA). As shown in Table 1, the oxygen barrier property of CS (Cur @ CMCPOA)-MCCPOA is 1.83×10 -17 , water vapor barrier performance is 2.19×10 -13 In contrast, the oxygen barrier and water vapor barrier properties of the CS (Cur@CMCPOA3) film are greatly improved, indicating that the introduction of MCCPOA improves the oxygen and water vapor barrier properties of the CS (Cur@CMCPOA)-MCCPOA film, and is better than most current studies. From the results of barrier properties, the introduction of MCCPOA film to prepare a double-layer chitosan composite film structure is conducive to improving the poor barrier properties of chitosan film, and broadens the application prospects of chitosan film in the packaging field.

[0068] Table 1

[0069]

[0070] Figure 5 It is the color responsiveness of chitosan(curcumin@carboxymethylcellulose palmitate)-cellulose palmitate membrane (CS(Cur@CMCPOA)-MCCPOA) membrane. Figure 5Figure a shows the color change of the same concentration of Cur@CMCPOA freeze-dried powder dissolved in phosphate buffers with different pH values, with a concentration of 1 mg / ml. As can be seen from the figure, when the pH is 11 and 12, the solution color changes from yellow to red, indicating that the curcumin emulsion does undergo a red shift in color in an alkaline environment; Figure c is the UV spectra corresponding to the different solutions in a. It is found from the figure that the UV absorption wavelengths at pH 11 and 12 have changed, which also indirectly confirms the reason for the color change of the curcumin emulsion; Figure 5 Figure b is the color change of the MCCPOA-CS (Cur@CMCPOA3) membrane after being immersed in buffer solutions of different pH values ​​for 5 minutes. From the results in the figure, it can be seen that MCCPOA-CS (Cur@CMCPOA3) also has color responsiveness. Under the environment of pH 11 and 12, the color of the membrane changed from yellow to red. Figure d is the sensitivity calculated by RGB of the color change of the MCCPOA-CS (Cur@CMCPOA3) membrane at different times at 1 cm above 0.8 mol / L ammonia water. A sensitivity greater than or equal to 25% indicates that it has color response as a smart cling film. From the figure, it can be seen that the sensitivity of the MCCPOA-CS (Cur@CMCPOA3) membrane is sufficient.

[0071] The above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a novel double-layer composite membrane, characterized in that: The steps include: S1, using palm oil as a raw material to prepare palmitoleic acid, and then further preparing palmitoleic acid into palmitoleic anhydride; S2: reacting the palmitoleic anhydride obtained in step S1 with carboxymethyl cellulose, and obtaining carboxymethyl cellulose palmitate after purification after the reaction; S3: adding the carboxymethyl cellulose palmitate obtained in step S2 to a pH-sensitive natural dye indicator to obtain a pH-sensitive carboxymethyl cellulose palmitate nanoemulsion; S4: adding natural polymer materials to the pH-sensitive carboxymethyl cellulose palmitate nanoemulsion obtained in step S3 to prepare a film; S5: forming a film of cellulose palmitate, and then adding the film-forming material obtained in step S4 onto the film to prepare a composite film, thereby obtaining the novel double-layer composite film; The preparation of cellulose palmitate in step S5 refers to step S1 and step S2, wherein carboxymethyl cellulose is replaced by cellulose.

2. The preparation method according to claim 1, characterized in that: In step S3, the pH-sensitive natural dye indicator is any one or more of anthocyanin, curcumin, carotene and shikonin.

3. The preparation method according to claim 1, characterized in that: The natural polymer material in step S4 is any one or more of agarose, chitosan, starch, cellulose, pectin, gelatin, zein and alginate.

4. The preparation method according to claim 1, characterized in that: In step S3, curcumin is added, and the process of adding curcumin is as follows: carboxymethyl cellulose palmitate and curcumin are firstly dissolved respectively, and then mixed and homogenized; the mass ratio of carboxymethyl cellulose palmitate to curcumin is 5 to 15:

1.

5. The preparation method according to claim 1, characterized in that: In the step S4, chitosan is added, and the mass fraction of chitosan is 2-5wt%.

6. The preparation method according to claim 1, characterized in that: The molar ratio of carboxymethyl cellulose to palmitoleic anhydride in step S2 is 1:3-6.

7. The preparation method according to claim 1, characterized in that: In step S2, p-toluenesulfonic acid is used as a catalyst and dimethyl sulfoxide is used as a co-solvent for dissolution; wherein the mass ratio of palm oleic anhydride to p-toluenesulfonic acid is 12:1, and the mass ratio of carboxymethyl cellulose to dimethyl sulfoxide is 1:

10.

8. The preparation method according to claim 1, characterized in that: The film formation in step S5 is carried out by using a tape casting method.

9. A novel double-layer composite membrane obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the novel double-layer composite film according to claim 9 in food packaging or fruit preservation.

Citation Information

Patent Citations

  • Preparation method of intelligent pH responding film for firmly retaining anthocyanidin

    CN108314792A

  • Production technology of degradable composite packaging film

    CN108559336A

  • Carboxymethyl chitosan / hydroformylated carboxymethyl cellulose composite membrane and preparation method thereof

    CN113185734A

  • Freshness indicating film based on purple sweet potato anthocyanin and / or curcumin as well as preparation method and application of freshness indicating film

    CN118671057A